Social capital as a determinant of subjective well-being among the elderly in urban Indonesia: Evidence from happiness and life satisfaction - Imalatul Royhana (Privietlab, 2026)
This study examined the relationship between social capital and the subjective well-being of the elderly in urban areas of Indonesia. Using cross-sectional data extracted from the 2014–2015 wave of the Indonesia Family Life Survey (IFLS) in 2014-2015, this study analyzes the influence of social capital on two main dimensions of subjective well-being: happiness and life satisfaction. Social capital is measured based on participation in different types of social activities, whereas subjective well-being is measured using scales of happiness and life satisfaction. To overcome the potential for endogeneity, the Two-Stage Predictor Substitution (2SPS) approach was used, with a multiple linear regression model in the first stage and an ordered logit model in the second stage. The results show that social capital does not significantly affect happiness but has a positive and significant effect on life satisfaction. Factors such as income and TV ownership contribute positively to both indicators of well-being, whereas low levels of education have a negative effect on happiness. The presence of children under the age of 15 in households is negatively associated with life satisfaction of the elderly. These findings confirm that the impact of social participation on the subjective well-being of the elderly is not uniform and depends on the dimensions of well-being measured; therefore, it is important to consider the context of old age and social environmental conditions when designing targeted social interventions.